Meta-Analysis of the Effect of Pelvic Floor Muscle Training in Reducing Urinary Incontinence and Elevating Quality of Life in Women - Addini, Ragil Aidil Fitriasari; Pamungkasari, Eti Poncorini; Murti, Bhisma (Indonesian Journal of Medicine, 2021)
Background: Urinary incontinence is a complaint of involuntary loss of urine and often occurs in women due to bladder dysfunction or weakened pelvic floor muscles. Pelvic floor muscle training (PMFT) is an exercise to treat urinary incontinence. This study aimed to analyze the effectiveness of pelvic floor muscle training to reduce urinary incontinence and improve quality of life in women.Subjects and Method: This was a systematic review and meta-analysis. The data was obtained through journal databases including PubMed, Science Direct, and Google Scholar by selecting articles published in 2010-2020. The keywords used were ("pelvic floor muscle training" OR "pelvic floor exercise" OR "kegel") AND ("urinary incontinence" OR "leaking urine" OR "urinary leakage") AND ("women" OR "female") AND "quality of life" AND "randomized controlled trial". The inclusion criteria were full paper articles with the Randomized Controlled Trial (RCT) research method. The size relationship used's of Mean SD, the intervention given was pelvic floor muscle training; female research subjects were 20-75 years old and experienced urinary incontinence. Search articles were done by using the PICO model. Population= Women with urinary incontinence, Intervention= pelvic floor muscle training, Comparison= not given PMFT, and Outcome= decreased urinary incontinence and improved quality of life. Articles were collected by using PRISMA flow diagrams and analyzed using the Revman 5.3 application.Results: Meta-analysis of 7 articles showed that pelvic floor muscle training could reduce urinary incontinence by 0.56 times higher compared to other interventions or no intervention (SMD= -0.56; 95% CI= -1.03 to -0.09; p= 0.020). Meta-analysis of 9 articles showed that pelvic floor muscle training improved quality of life by 0.32 times higher compared to other interventions or no intervention (SMD= -0.32; 95% CI= -0.66 to 0.02; p=0.070).Conclusion: Pelvic Floor Muscle Training (PMFT) reduces urinary incontinence and improves the quality of life in women.Keywords: pelvic floor muscle training, urinary incontinence, quality of lifeCorrespondence: Ragil Aidil Fitriasari Addini. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: ragilaidilfa@gmail.com. Mobile: 089609133808.Indonesian Journal of Medicine (2021), 06(03): 258-270https://doi.org/10.269¬11/theijmed.2021.06.03.03